Adaptação do ensaio roda-de-borracha para avaliação do desgaste abrasivo a três corpos de rolos poliméricos de correias transportadoras - Pacholok, Daniel Estefano (2021)
Due to the demand for the improvement of production processes in the mining sector, the enhancement of components is essential to avoid failures. Ore conveyor belt rollers are constantly subject to two and three-body abrasion só that a metal rollerŠs jamming due to bearing failure severs abrasion, and sharp edges capable of cutting the belt are exposed. The alternative to avoid failure is the use of polymeric rollers, which are also lighter. In this sense, this work aims to characterize and rank, according to abrasion resistance, polymeric rollers of different compositions through experimental simulation of wear phenomena. In order to carry out this study, an instrumented and adapted rubber wheel test equipment was built, allowing the use of rings, and só reproducing the contact between belt and roller. Samples of three different polymers were analyzed: HDPE + CB (High Density Polyethylene) with carbon black (CB) present in two different weight percentages (2,3 % and 3,6 %), from two different suppliers, UHMWPE (Ultra High Molecular Weight Polyethylene) and HDPE + FG (High Density Polyethylene) with Ąberglass (FG) additives; further tests were carried out with a sample of AISI 1020 steel from a roller worn in Ąeld, which was the reference material. Two conĄgurations were used: Ąxed samples, reproducing the situation of a jammed roll; and rotating samples, reproducing a condition of a running roller. For tests with Ąxed samples, a normal force of 200 Newton and a total test time of 10 minutes (1420 meters) were applied. For rotating samples, tests were performed with a normal force of 250 Newton and 40 hours duration (344.720 meters). The samples were characterized by gravimetry, evaluation of wear marks with subsequent calculation of the worn volume and mass. The worn surface was analyzed by SEM, in order to investigate the abrasion mechanisms, as well as to correlate them with the results obtained and to compare them with the mechanisms observed in a roller worn in Ąeld and also with results of scratching tests with the same materials. It were noticed dissimilar behaviors for friction and wear between the different experimental approaches of rubber wheel; as for wear mechanisms, in tests with Ąxed samples, there was a predominance of micro-grooving in UHMWPE, micro-cutting in both HDPE + CB, micro-cracking in HDPE + FG and a combination of micro-grooving, indentation and micro-cut in steel. In tests with rotating sample the wear mechanism observed for all samples was indentation due to the bearing of particles, and micro-cracking in the HDPE+FG sample. The results obtained in both rubber wheel experimental approaches reveal the abrasive wear resistance hierarchy as: UHMWPE > HDPE+CB36 > HDPE+CB23 > STEEL > HDPE+FG.